Free-Space Optical Space Division Multiplexing for Smart Healthcare - Amphawan, Angela; Ayaz, Anwar *; Ong, Seng Kai *; Sutanto, Juliana; Neo, Tse Kian; Anwar, Khoirul (IEEE, 2023)
The rise in the number of patients during the pandemic has prompted hospitals to extend their services beyond in-person visits and increase contactless patient monitoring. This paper reviews the landscape of smart healthcare based on free space optics and space division multiplexing for reducing contact between doctors and patients. A conceptual framework for a FSO space division multiplexing system is presented for contactless patient monitoring using OAM modes. Contactless free space optical technology is poised to make healthcare services more relevant to the lifestyle of the modern citizen in smart cities.